Pemilihan Penilaian Karyawan Menggunakan Metode Hybrid ROC-MOORA - Sitti Nur Alam; Fauzi Fauzi; Firman Santoso; Saludin Saludin; Monanda Rio Meta (Journal of Computer System and Informatics (JoSYC), 2023)
Apprentices are employees who work within the context of a real learning process in the workplace to hone skills and self-quality in achieving maturity in learning science in the world of education, apprentices are also commonly referred to as temporary employees who have a short period of time permitting work in a company , it is not uncommon for a company to appoint an apprentice immediately to become a permanent worker because it is considered capable of minimizing the time in the process of selecting new employees needed to fill employee positions required by a company, several companies also collaborate a lot with a university to accept participants educate them to be able to work in the company they want. In determining an apprentice to become a permanent employee of the company, of course, careful assessment and consideration is needed as is done in other employee selection processes, to eliminate subjective and unfair selection and to improve the quality of the company's assessment of target apprentices who will be appointed as permanent employees. need to build a decision-making system. This is widely applied by other leading companies. In this research, the application of a decision support system was carried out in determining the apprentice's assessment to be selected as a permanent employee of a company using the combination method by applying the weight of the data assessment using the ROC method and the MOORA method ranking method, the results obtained were 0.365 the highest point from the acquisition of the value obtained out of 10 apprentices, the highest score is data recommended by the system as interns who have the best potential to become permanent employees of the company.